Pelatihan Pengolahan Sayuran Hidroponik Dan Pemasaran Dalam Meningkatkan Pendapatan Di Desa Sejegi Kecamatan Mempawah Timur - Hairil Anwar; Hardilina; Indah Sulisdiani; Nahot Tua Parlindungan Sihaloho (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2023)
The PKK group and the Farmers' group in Sejegi Village, East Mempawah District, Mempawah Regency have succeeded in cultivating vegetable crops using hydroponic techniques, such as spinach, pakcoy, and lettuce. As an effort to improve the community's economy and utilize the potential of existing land. However, there are problems related to hydroponic vegetable harvesting carried out by partners, namely vegetables that are harvested only in the form of 1 product, namely raw vegetables that are sold to the market or sold directly to household consumers. Partners do not have knowledge about processing hydroponic vegetable products into various products or product diversification. Besides that, partners do not understand how to package packaging products for processed products from hydroponic vegetable plants and a lack of understanding of the importance of branding on products that will give an attractive appearance to a product so that consumers become interested in buying these products, and another problem is the lack of knowledge about how to marketing products online using social media such as Instagram, Facebook, and WhatsApp. The result of this community service activity is an increase in public knowledge in processing hydroponic vegetables and good marketing methodsThe method used is lecture, discussion, and practice. The final expected goal of this socialization and training is for the target partners to have knowledge in developing their business so that they can increase family income.